Epidemiology and antimicrobial resistance of Mycobacterium spp. in the United Arab Emirates: a retrospective analysis of 12 years of national antimicrobial resistance surveillance data - Thomsen, Jens; Abdulrazzaq, Najiba M.; Nyasulu, Peter S.; Al Hosani, Farida; Habous, Maya; Weber, Stefan; Jabeen, Fouzia, The UAE AMR Surveillance Consortium; Menezes, Godfred Antony; Moubareck, Carole Ayoub; Senok, Abiola; Everett, Dean B.; et al. (Frontiers in Public Health, 2024)
Introduction The Eastern Mediterranean Regional Office (EMRO) region accounts for almost 8% of all global Mycobacterium tuberculosis (TB) cases, with TB incidence rates ranging from 1 per 100,000 per year in the United Arab Emirates (UAE) to 204 per 100,000 in Djibouti. The national surveillance data from the Middle East and North Africa (MENA) region on the epidemiology and antimicrobial resistance trends of TB, including MDR-TB remains scarce. Methods A retrospective 12-year analysis of N = 8,086 non-duplicate diagnostic Mycobacterium tuberculosis complex (MTB complex) isolates from the UAE was conducted. Data were generated through routine patient care during the 2010–2021 years, collected by trained personnel and reported by participating surveillance sites to the UAE National Antimicrobial Resistance (AMR) Surveillance program. Data analysis was conducted with WHONET, a windows-based microbiology laboratory database management software developed by the World Health Organization Collaborating Center for Surveillance of Antimicrobial Resistance, Boston, United States (https://whonet.org/). Results A total of 8,086 MTB-complex isolates were analyzed. MTB-complex was primarily isolated from respiratory samples (sputum 80.1%, broncho-alveolar lavage 4.6%, pleural fluid 4.1%). Inpatients accounted for 63.2%, including 1.3% from ICU. Nationality was known for 84.3% of patients, including 3.8% Emiratis. Of UAE non-nationals, 80.5% were from 110 countries, most of which were Asian countries. India accounted for 20.8%, Pakistan 13.6%, Philippines 12.7%, and Bangladesh 7.8%. Rifampicin-resistant MTB-complex isolates (RR-TB) were found in 2.8% of the isolates, resistance to isoniazid, streptomycin, pyrazinamide, and ethambutol, was 8.9, 6.9, 3.4 and 0.4%, respectively. A slightly increasing trend of resistance among MTB-complex was observed for rifampicin from 2.5% (2010) to 2.8% (2021). Conclusion Infections due to MTB-complex are relatively uncommon in the United Arab Emirates compared to other countries in the MENA region. Most TB patients in the UAE are of Asian origin, mainly from countries with a high prevalence of TB. Resistance to first line anti-tuberculous drugs is generally low, however increasing trends for MDR-TB mainly rifampicin linked resistance is a major concern. MDR-TB was not associated with a higher mortality, admission to ICU, or increased length of hospitalization as compared to non-MDR-TB.